Chemical characterization and antioxidant potential of Maytenus guianensis from Alto Solimões - Holanda, Naíra Assunção de Sá; Santiago, Sarah Raquel Silveira da Silva; Silva, Elizangela Farias da; Salimo, Zeca Manuel; Santiago, Paulo Alexandre Lima (Acta Scientiarum. Biological Sciences, 2025)
Maytenus guianensis has several biological activities, including antioxidant, anti-inflammatory, antimicrobial and antiparasitic properties. Previous studies have shown that terpenes and flavonoids are the most prevalent compounds in its chemical composition. Despite its potential use in traditional medicine, its phytochemistry is little explored in the Amazon region, especially in the Alto Solimões. This study analyzed the chemical profile and antioxidant potential of M. guianensis collected in the Alto Solimões, and identified the probable compounds with antioxidant activity in the hydroethanolic extract by means of mass spectrometry. The botanical material was collected, sanitized, dried, fragmented, extracted with 70% ethanol, and filtered. The samples were filtered, dried, weighed, packaged, and sent to Manaus, AM, for antioxidant activity determination and mass spectrometry analysis. As a result, extract yield was highest in the leaves (21%), followed by the roots (13.6%), stem (8.5%), and branches (3.2%). The root extract and branches had the highest antioxidant activity at 99.7%. Mass spectrometry definitively characterized seven compounds in the root extract: kaempferol-3-O-galactosyl (1-2) rhamnoside, amyrin, and taraxerol; a glycosylated flavonol in the leaf extract; quercetin-3-O-galactosyl (1-2) rhamnoside in the root extract; lupeol/friedelin; and betulinic acid in the twig extract. These results clearly demonstrate the high pharmacological potential of M. guianensis and justify further research with medicinal plants in the Alto Solimões region, promoting the appreciation of this species.